2019
DOI: 10.1115/1.4044687
|View full text |Cite
|
Sign up to set email alerts
|

Nonaxisymmetric Study of Tip Leakage Flow in a Centrifugal Compressor With a Volute During Stall Process

Abstract: Tip leakage flow (TLF) patterns, which affect compressor performance, are closely related to compressor stability. To date, minimal attention has been given to circumferential nonuniformity of the TLF in a centrifugal compressor with a nonaxisymmetric volute structure. In this study, the circumferential difference of the TLF in a centrifugal compressor with a volute during the stall process is analyzed. The circumferential nonuniformity of tip leakage vortex (TLV) trajectories, loading distribution near the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The static pressure circumferential double-peak distribution also leads to significant differences in the TLF losses of different blades. The results of the references 28,29 showed that the TLF loss of the blade affected by HP1 is always the largest at any instance. With the development of the stall process, the TLF loss of the blade affected by HP2 gradually increases until it is very close to that affected by HP1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The static pressure circumferential double-peak distribution also leads to significant differences in the TLF losses of different blades. The results of the references 28,29 showed that the TLF loss of the blade affected by HP1 is always the largest at any instance. With the development of the stall process, the TLF loss of the blade affected by HP2 gradually increases until it is very close to that affected by HP1.…”
Section: Introductionmentioning
confidence: 99%
“…27 A larger a indicates that the compressor is closer to the stall. The studies 28,29 showed that for a centrifugal compressor, the values of a at different circumferential positions are different, and there are two peaks in the circumferential direction, which corresponds to the circumferential position of the impeller inlet affected by the two high static pressure bands HP1 and HP2. The static pressure circumferential double-peak distribution also leads to significant differences in the TLF losses of different blades.…”
Section: Introductionmentioning
confidence: 99%
“…The intense secondary flow in the impeller also affects the rotating stall in the diffusor by causing circumferential distortion of its inlet flow, resulting in the hub-corner separation on diffusor vanes (Marsan et al, 2015). The circumferential non-uniformity for most centrifugal compressors is caused by volute governs the evolution of the rotating stall cells (Niu et al, 2020;Yang et al, 2019). The generation and disappearance process of rotating stall cells are observed due to the pressure distortion along the circumferential direction in a vaneless diffuser.…”
Section: Introductionmentioning
confidence: 99%